The study of spasmolytic activity, acute and chronic toxicity of piperidine derivative – NA-323 substance (Eurasian Journal of Ecology, 2016)
In experiments on rats and mice the spasmolytic activity, acute and chronic toxicity of including complex of oxalate 1-(2-etoxietil)-4-(hexine-1-il)-4-propionil-oxipiperidine derivate – NA-323 substance were investigated. It was established the pronounced spasmolytic activity of this substance, which is expressed in suppression of acetylcholineinduced tonic contraction of a gut segment. In experiments it was shown an absence of acut and chronic toxicity of NA-323 substance in the dozes of 1,0,10,0 и 50 mg/kg
Keywords: mice; rats; experiment; spasmolytic activity; acute and chronic toxicity.